Change Management in Implementing Online Learning Systems at University in Aceh - Muhammad Rezeki Muamar; Diding Nurdin; Marwan Marwan; Sonny Muhammad Ikhsan Mangkuwinata (STAI Hubbulwathan Duri, 2023)
The University's attempt to introduce online learning was met with a number of obstacles. Therefore, effective implementation of online learning in higher education necessitates using change management strategies. This research aims to help Universitas Almuslim plan for the successful introduction of online education. The research is qualitative research. The respondent of the research are leaders, lecturers and students of Almuslim University. The respondents were selected through the purposive sampling method. In addition, the data of the research were collected through interviews. The research consists of three distinct parts. First, a Prosci ADKAR Checklist change management gap analysis was performed on Universitas Almuslim's efforts to incorporate online learning. Second, firm approaches to managing transitions. At long last, Universitas Almuslim has developed a strategy for distance education. The research produced a plan for introducing online education at Universitas Almuslim through change management activities. The current state, the transition state, and the future state make up the roadmap's three states. The processes of becoming aware of things and of wanting them are outlined. Then, the steps required to acquire the necessary knowledge and skills are outlined. Finally, the future state's abilities and reinforcements are outlined.